Pembuatan Media Pembelajaran Al-Qur’an Ramah Lingkungan di TPA Miftahul Ulum Dusun Pohjenggel Desa Katikan Kecamatan Kedunggalar - Ana Zahrotul nafiah; Anas Ma,ruf; Nur Avivah; Wafi Faqih Ahmad Al Ghozali; Rela Mar'ati (Jurnal Abdikarya Pembangunan, 2023)
Abstract: The community in Pohjenggel, Katikan considers the role of Miftahul Huda Landfill important in the field of religious education for their children, especially in the Covid-19 Pandemic situation where learning in schools is carried out online and is considered less optimal so that the existence of TPA in that place which is still carried out offline (face-to-face) by implementing health protocols is felt to be very useful. However, the problem in the landfill is the lack of Qur'anic learning media that supports children's learning, so that learning so far has been less than optimal. This service uses the Participation Action Research (PAR) method where researchers are positioned as facilators to empower local potential to solve problems, namely in the form of providing environmentally friendly Qur'an learning media by utilizing waste from used goods around the landfill environment. The PAR research cycle carried out is in the form of knowing the problem, then together with the community analyze the problem and determine the actions to be taken, then take action and reference the actions taken so that the activities are in accordance with the objectives. The result of this study is in the form of a change in the understanding of landfill residents about the importance of maintaining the balance of nature, one of which is by recycling goods that are not useful and have teamwork in making environmentally friendly learning media. The change in attitude also shows the attitude of TPA students who are more enthusiastic in participating in lessons because of the interesting media. Keywords: Environment, Learning media, Qur;an Education, Santri Abstract: Masyarakat di Dusun Pohjenggel Desa Katikan mengangap penting peran TPA Miftahul Huda dalam bidang pendidikan agama untuk anak-anak mereka apalagi dalam situasi Pandemi Covid-19 dimana pembelajaran di sekolah dilakukan secara daring dan dirasa kurang maksimal sehingga keberadaan TPA di tempat tersebut yang masih dilakukan secara luring (tatap muka) dengan menerapkan protocol kesehatan dirasakan sangat bermanfaat. Namun permasalahan di TPA tersebut adalah kurang media pembelajaran Al-qur’an yang menunjang belajar anak, sehingga pembelajaran selama ini berjalan kurang maksimal. Pengabdian ini menggunakan metode Participation Action Research (PAR) yang fokusnya untuk memberdayakan potensi setempat dalam menyelesaikan masalah yaitu berupa penyediaan media pembelajaran Al-Qur’an yang ramah lingkungan dengan memanfaatkan limbah barang bekas yang ada di sekitar lingkungan TPA. Siklus PAR yang dilakuan berupa tahap mengetahui permasalahan, kemudian menganalisa permasalahan dan menentukan aksi yang akan dilakukan, selanjutnya melakukan aksi dan refleksi atas aksi yang dilakukan agar kegiatan sesuai dengan tujuan. Hasil pengabdian ini berupa berubahnya pemahaman warga TPA tentang pentingnya menjaga keseimbangan alam salah satunya dengan mendaur ulang barang yang tidak berguna serta memiliki keteampilan dalam membuat media pembelajaran ramah lingkungan. Perubahan sikap juga menunjukan sikap santri TPA yang lebih antusias dalam mengikuti pelajaran karena adanya media yang menarik. Keywords: Media Pembelajaran, lingkungan, Santri, Taman Pendidikan Al-Qur’an